Understanding Burnout among Head-and-neck Cancer Surgeons: A Pan-India Survey and Literature Review - Manish Tiwari; Bharat Kumar Sarvepalli; M. N. Viswanath; Apurba Das; Vibhaben Vatsal Patel; Reshma Helode; Moni Abraham Kuriakose (Journal of Head & Neck Physicians and Surgeons)
Background: Burnout, characterized by emotional exhaustion (EE), depersonalization (DP), and reduced personal accomplishment (PA), is a growing concern among healthcare professionals, especially surgeons. Head-and-neck oncosurgeons face heightened burnout risks due to complex surgeries, emotionally taxing patient interactions, and systemic challenges. Objective: To assess the prevalence and severity of burnout among head-and-neck oncosurgeons in India, identify contributing factors, and propose strategies for mitigation. Methods: A cross-sectional survey was conducted among 100 head-and-neck oncosurgeons in India, with 81 valid responses. Burnout was measured using the Maslach Burnout Inventory – Student Survey (MBI-SS). Descriptive statistics, correlation analyses, and multiple regression models were used to evaluate burnout levels and predictors. Internal consistency of the MBI-SS was assessed using Cronbach’s alpha. To complement the survey findings, a systematic literature review was conducted. Results: Among the 81 respondents, 49.4% met the burnout criteria. Most affected surgeons experienced mild burnout (n = 32), with 2 cases of severe burnout. Mean scores for burnout dimensions were EE: 15.05, DP: 6.50, and PA: 28.88. Weak correlations were observed between burnout and factors like work hours, number of surgeries, and experience. Regression analysis revealed DP as a significant predictor of EE (P < 0.001), but PA did not significantly influence EE or DP. Internal consistency of MBI-SS was poor across dimensions (Cronbach’s α < 0.2), indicating limitations in tool reliability for this population. Conclusion: Nearly half of Indian head-and-neck oncosurgeons surveyed exhibited signs of burnout, with emotional detachment emerging as a key driver of emotional exhaustion. Traditional workload metrics showed limited predictive value. Targeted institutional interventions, improved mental health support, and refined burnout assessment tools are essential to mitigate burnout and ensure sustainable surgical practice.